2017
DOI: 10.11646/zootaxa.4268.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genome and taxonomic revision of Cardiodactylus muiri Otte, 2007  (Gryllidae: Eneopterinae: Lebinthini)

Abstract: In the present study, we report the high-coverage complete mitochondrial genome (mitogenome) of the cricket Cardiodactylus muiri Otte, 2007. The mitogenome was sequenced using a long-PCR approach on an Ion Torrent Personal Genome Machine (PGM) for next generation sequencing technology. The total length of the amplified mitogenome is 16,328 bp, representing 13 protein-coding genes, 22 transfer RNA genes, two ribosomal RNA genes and one noncoding region (D-loop region). The new sets of long-PCR primers reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 553 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“… 2019a ), C. muiri NC_037914 (Dong et al. 2017 ), T. hibinonis NC_034797 (Li et al. 2019 ), O. sinensis NC_034799 (Li et al.…”
Section: Resultsmentioning
confidence: 99%
“… 2019a ), C. muiri NC_037914 (Dong et al. 2017 ), T. hibinonis NC_034797 (Li et al. 2019 ), O. sinensis NC_034799 (Li et al.…”
Section: Resultsmentioning
confidence: 99%
“…The codons of cox1 in some species of Grylloidea start with ATT or ATC. The Oecanthidae Oecanthus sinensis (Oecanthinae), Truljalia hibinonis (Podoscirtinae), and the Trigonidiidae Trigonidium sjostedti (Trigonidiinae) use ATT as the start codon of cox1 ; ATC is the start codon of cox1 in the two Gryllidae Eneopterinae Cardiodactylus muiri and Pseudolebinthus lunipterus (Song et al 2016; Dong et al 2017; Li et al 2019; Salazar et al 2020). Most species in Gryllidae Gryllinae have TCG as the start codon of cox1 (Yang et al 2016; Zhou et al 2017; Ma et al 2019b; Chang et al 2020; Sanno et al 2021; Torson et al 2021; Yang et al 2021), which is also found in the Gryllidae Eneopterinae Xenogryllus marmoratus and Oecanthidae Oecanthinae Oecanthus rufescens , and in the Phalangopsidae Cacoplistes rogenhoferi and Meloimorpha japonica (Cacoplistinae) (Ma et al 2019a; Zhou et al 2017; Ma & Li 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al (2017) described the arrangements in 59 ensiferan mitogenomes and their phylogenetic tree recovered the sister relationship between Grylloidea and Gryllotalpoidea based on four Grylloidea species (including Oecanthinae and Gryllinae) and three Gryllotalpoidea species (including Myrmecophilinae and Gryllotalpinae). Dong et al (2017) presented complete mitogenome of Cardiodactylus muiri Otte, 2007 and constructed phylogenetic trees of Eneopterinae and other species in the family Gryllidae based on the sequences of c ytb and rrnS respectively. Chang et al (2020) reported the phylogenetic relationship of 171 species in Orthoptera by using mitogenomes and represented their divergence time and evolution rate along with wing types.…”
Section: Introductionmentioning
confidence: 99%
“…All three cricket mitogenomes exhibit strong GC-skew values ranging from -0.345 to -0.332, a characteristic shared with species of Eneopterinae and Gryllinae (Ensifera) ( Dong et al, 2017 ). These negative GC skew values indicate an excess of C relative to G in these mitogenomes ( Dong et al ., 2017 ; Ma et al, 2019 ). The AT-skew values ranged between Endecous (0.044 and 0.063) and D. nigrofasciatus (-0.011).…”
Section: Discussionmentioning
confidence: 99%